PKM Peningkatan Mutu Dan Produksi VCO Tradisional Pada Industri Rumah Tangga di Desa Baumata Kecamatan Taebenu Kabupaten Kupang - Muntasir Muntasir; Tadeus AL. Regaletha; Yoseph Kenjam (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Community groups of farmers and plantation workers picking old coconuts are only sold in the market in raw form. They have not received an empowerment program in processing agricultural and plantation products. On the other hand, there are small household businesses that produce VCO with simple equipment, manually and by hand, so that production capacity is limited. They have not received science and technology assistance from universities. This service program (PKM) is located in Baumata Village. The purpose of PKM is to increase the potential of agricultural products as products that increase household income, which leads to an increase in community welfare. PKM is carried out by providing a grating machine and squeezing equipment. The activity stages are activity planning and partner survey, intervention, counseling and advice. This PKM increases the added value and selling value of coconut products. The fruit picked from coconut trees ranges from 10-40 seeds per day sold at a price of Rp. 3,000. Average income in the range of Rp. 30,000.00 - Rp. 100,000.00. Empowerment of community groups and small household businesses provides added value in terms of income and increases the welfare of farmers. Coconut is produced into VCO. VCO products are sold in 250 mL packages for Rp. 50.000,00 then farmers get added value and product processing value. 40 coconut seeds produced into VCO will produce 5000 mL of VCO equivalent to 20 bottles of 250 mL VCO or Rp. 1,000,000. Empowerment of this community group has the ability to produce VCO products quickly, easily, simply, has good sanitation and quality production, has P-IRT labeling and permits to be marketed as a family or group business. This increases family income and provides economic value for coconut products.